Operator‐informed risk assessment tool: Opportunities and barriers to support risk management practices. Issue 5 (3rd October 2022) - Lane, Kaycie; Fuller, Megan; Gagnon, Graham
Abstract: Successfully implementing water safety plans (WSPs) in small, municipal drinking water systems is understudied in affluent jurisdictions where WSPs are not required by regulations. We piloted a computer‐based risk assessment survey in eight municipal water systems in Nova Scotia, Canada to evaluate the benefits and challenges of implementing risk assessment strategies in non‐WSP jurisdictions. Semi‐structured interviews were conducted with water operators and managers to gather feedback on the risk assessment survey and process. Results indicated difficulties quantifying risk despite streamlining the risk identification process, resulting in key informants viewing the risk assessment as strictly diagnostic and unlikely to be integrated into operational practice if not required. We identified a need to shift water system culture from a regulatory‐based to a knowledge‐based mindset for successful risk assessment implementation. Clear lines of communication, increased understanding of risk, and commitment to improvement are critical to shifting water system culture toward a risk‐based water quality management approach.